Seroprevalence of SARS-CoV-2 antibodies among 925 staff members in an urban hospital accepting COVID-19 patients in Osaka prefecture, Japan: A cross-sectional study. Issue 25 (25th June 2021) - Nishida, Tsutomu; Iwahashi, Hiromi; Yamauchi, Kazuhiro; Kinoshita, Noriko; Okauchi, Yukiyoshi; Suzuki, Norihiro; Inada, Masami; Abe, Kinya
Abstract : Abstract: The subclinical severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection rate in hospitals during the pandemic remains unclear. To evaluate the effectiveness of our hospital's current nosocomial infection control measures, we conducted a serological survey of anti-SARS-CoV-2 antibodies (immunoglobulin [Ig] G) among the staff of our hospital, which is treating coronavirus disease 2019 (COVID-19) patients. The study design was cross-sectional. We measured anti-SARS-CoV-2 IgG in the participants using a laboratory-based quantitative test (Abbott immunoassay), which has a sensitivity and specificity of 100% and 99.6%, respectively. To investigate the factors associated with seropositivity, we also obtained some information from the participants with an anonymous questionnaire. We invited 1133 staff members in our hospital, and 925 (82%) participated. The mean age of the participants was 40.0 ± 11.8 years, and most were women (80.0%). According to job title, there were 149 medical doctors or dentists (16.0%), 489 nurses (52.9%), 140 medical technologists (14.2%), 49 healthcare providers (5.3%), and 98 administrative staff (10.5%). The overall prevalence of seropositivity for anti-SARS-CoV-2 IgG was 0.43% (4/925), which was similar to the control seroprevalence of 0.54% (16/2970) in the general population in Osaka during the same period according to a government survey conducted with the same assay. Seropositive rates did not significantly differ according to job title, exposure to suspected or confirmed COVID-19 patients, or any other investigated factors. The subclinical SARS-CoV-2 infection rate in our hospital was not higher than that in the general population under our nosocomial infection control measures.